Implementasi Peraturan Daerah Provinsi Lampung Nomor 19 Tahun 2014 tentang Penggunaan Jalan Umum dan Jalan Khusus Angkutan Hasil Tambang Perspektif Siyasah Tanfidziyyah - Dhea Aulia Hazizah; Jayusman; Nurasari (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research is motivated by the problem of coal cargo transportation that still uses large-capacity trucks on public roads, allegedly violating the implementation of Article 4 of Lampung Provincial Regulation Number 19 of 2014 concerning the use of public roads and special roads for the transportation of mining products and plantation company products. The focus of this research is a review of Fiqh Siyasah Tanfidziyyah on the implementation of this article. The research method uses a qualitative approach with interview, observation, and documentation techniques. The research sample consisted of 8 people: 2 employees of the Lampung Province Transportation Agency, 3 coal truck drivers, 2 residents of Panjang, and 1 stockpile guard. The results show that the Siyasah Tanfidziyyah review of the implementation of public road provisions in Article 4 of the Provincial Regulation is not yet appropriate because coal transportation still uses public roads, resulting in road damage due to excessive loads. This condition is caused by several factors: lack of supervision from relevant authorities, limited availability of special road infrastructure for mining transportation, and weak enforcement of sanctions against violations. Thus, the implementation of the Provincial Regulation has not been optimal and requires improvements in the supervision system and stricter law enforcement